PEWARNAAN MENGGUNAKAN ZAT WARNA DIREK DENGAN PENGENTAL DALAM PEMBUATAN ’KAIN TRITIK - santoso, ratna endah; Josef, Adji Isworo; Affanti, Tiwi Bina; -, Sarwono -; Utami, Lira Anundita (Institut Seni Indoensia Surakarta, 2022)
This research was conducted to create a method for dyeing trick using Direct dyestuff. The developed coloring is staining using thickener but not used through printing. The study is concentrated on the results of the dyeing process on tricks with Direct dyestuff with thickener. The method used is descriptive qualitative in the discussion of the coloring results. From the results of this study, it was found that dyeing with Direct dyestuff using a thickener in the manufacture of tritik fabric produced tritik motifs. The sharpness of the resulting motif varies at each level of thickener concentration. The thickener concentrations used in this study were 5 g/l, 20 g/l, 35 g/l, 50 g/l, 65 g/l, and 80 g/l, for every 1 liter of dye solution. With a low thickener concentration, the tritik motif looks less sharp, the color aging is higher, and the staining results look more even. The unevenness that arises due to the use of high concentrations of thickener is seen to form a marble-like pattern. The sharpness of the resulting motif in this staining does not always correspond to the high concentration of the thickener. Variations in the non-sharpness of the colored motifs can also appear on one piece of tritik fabric that is produced.